Support for, and perceived effectiveness of, the UK soft drinks industry levy among UK adults: cross-sectional analysis of the International Food Policy Study - David Hammond; Jean Adams; Martin White; David Pell; Tarra Penney; Lana Vanderlee (BMJ Open)
Objectives To answer four questions: What are attitudes, knowledge and social norms around sugar-sweetened beverages (SSBs)? What are current levels of trust in messages on SSBs? What is current support for, and perceived effectiveness of, the UK soft drinks industry levy (SDIL)? What is the association between attitudes, knowledge, social norms, trust, SSB consumption and sociodemographic factors; and support for, and perceived effectiveness of, the SDIL?Design Cross-sectional online survey.Setting UK.Participants UK respondents to the 2017 International Food Policy Study aged 18–64 years who provided information on all variables of interest (n=3104).Outcome measures Self-reported perceived effectiveness of, and support for, the SDIL.Results Most participants supported the SDIL (70%), believed it would be effective (71%), had a positive attitude to SSBs (62%), had knowledge of the link between SSBs and obesity (90%), and trusted messages from health experts (61%), but not those from the food and beverage industry (73%). Nearly half (46%) had negative social norms about drinking SSBs. In adjusted models, older age, non-consumption of SSBs, social norms to not drinks SSBs, knowledge of the link between SSBs and obesity and trust in health expert messages were associated with greater support for the SDIL, whereas having dependent children and trusting messages from the food and beverage industry were associated with less support. In adjusted models, older age was associated with lower perceived effectiveness of the SDIL, whereas social norms to not drink SSBs, negative attitudes to SSBs and trusting messages from health experts and the food and beverage industry were associated with greater perceived effectiveness.Conclusions There was strong support for the SDIL and belief that it would be effective. Those with more ‘public health’ orientated norms and trust were generally more likely to support the SDIL or believe that it would be effective.